Fungsi Periklanan Sebagai Alat Pengembangan Dakwah Pada Media Sosial - Erwan Effendy; Nurul Aulia; Nur Alhikmah; Boby Anasta (Jurnal Ilmiah Wahana Pendidikan, 2023)
Dakwah is an appeal to invite people to do good and forbid evil. This inviting activity can be done in various ways and using various media, one of the alternative media that can be used in preaching is by using advertisements. Da'wah activities are growing along with the development of science and technology. Islamic da'wah as a manifestation of a Muslim's faith can be socialized through various media without reducing the meaning and purpose of Islamic da'wah. Da'wah can adjust to the media that is currently developing in society. Preachers can take advantage of various existing media in preaching, so that the reach of preaching is broad and can even cover the whole world. Islamic da'wah inserted through advertisements with various kinds of things such as on Instagram, Facebook, YouTube, tik tok and others.